Monosynaptic Input Mapping of Diencephalic Projections to the Cerebrospinal Fluid-Contacting Nucleus in the Rat - Si-Yuan Song; Ying Li; Xiao-Meng Zhai; Yue-Hao Li; Cheng-Yi Bao; Cheng-Jing Shan; Jia Hong; Jun-Li Cao; Li-Cai Zhang (Frontiers Media S.A., 2020)
Objective: To investigate the projections the cerebrospinal fluid-contacting (CSF-contacting) nucleus receives from the diencephalon and to speculate on the functional significance of these connections.Methods: The retrograde tracer cholera toxin B subunit (CB) was injected into the CSF-contacting nucleus in SD rats according to the experimental formula of the stereotaxic coordinates. Animals were perfused 7-10 days after the injection, and the diencephalon was sliced at 40 μm with a freezing microtome. CB-immunofluorescence was performed on all diencephalic sections. The features of CB-positive neuron distribution in the diencephalon were observed with a fluorescence microscope.Results: The retrograde labeled CB-positive neurons were found in the epithalamus, subthalamus, and hypothalamus. Three functional diencephalic areas including 43 sub-regions revealed projections to the CSF-contacting nucleus. The CB-positive neurons were distributed in different density ranges: sparse, moderate, and dense.Conclusion: Based on the connectivity patterns of the CSF-contacting nucleus that receives anatomical inputs from the diencephalon, we preliminarily assume that the CSF-contacting nucleus participates in homeostasis regulation, visceral activity, stress, emotion, pain and addiction, and sleeping and arousal. The present study firstly illustrates the broad projections of the CSF-contacting nucleus from the diencephalon, which implies the complicated functions of the nucleus especially for the unique roles of coordination in neural and body fluids regulations.